2016
DOI: 10.1097/md.0000000000005617
|View full text |Cite
|
Sign up to set email alerts
|

Low mortality but increasing incidence of Staphylococcus aureus endocarditis in people who inject drugs

Abstract: Staphylococcus aureus is a leading cause of infective endocarditis in people who inject drugs (PWID). The management of S aureus endocarditis (SAE) in PWID can be problematic. The objective of this retrospective observational study was to assess the epidemiology, clinical characteristics, and mortality of S aureus endocarditis (SAE) in PWID in Stockholm, Sweden.The Department of Infectious Diseases at the Karolinska University Hospital serves as a regional referral center for drug users with severe infections.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
6
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 37 publications
2
14
6
3
Order By: Relevance
“…In this study, we identified a substantial and progressive increase in the risk of infective endocarditis among people who inject drugs, beginning in 2010. This increase in overall risk [5][6][7] and the higher risk among men 18 is consistent with findings from other jurisdictions. We expected this increase to occur in the fourth quarter of 2011, when traditional controlled-release oxycodone was removed from the Canadian market; however, the increase in risk predated this event.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, we identified a substantial and progressive increase in the risk of infective endocarditis among people who inject drugs, beginning in 2010. This increase in overall risk [5][6][7] and the higher risk among men 18 is consistent with findings from other jurisdictions. We expected this increase to occur in the fourth quarter of 2011, when traditional controlled-release oxycodone was removed from the Canadian market; however, the increase in risk predated this event.…”
Section: Discussionsupporting
confidence: 90%
“…10 This definition includes patients aged 18 to 55 years who had hospital admissions in the preceding 6 months with diagnoses of opioid, stimulant or combined drug abuse, or infection with hepatitis C. The age restriction reflects the distribution of ages in previously described cohorts of people who inject drugs and in our own validation study. 7,11,12 Compared with chart review, this definition has been shown to have a sensitivity of 93% and a positive predictive value of 83%. 10 We defined infective endocarditis using administrative codes (Supplemental Table 3, Appendix 1).…”
Section: Study Populationmentioning
confidence: 99%
“…IV drug abuseKUH has a special ward for addicts with infections, with an uptake area covering Stockholm County Council (approximately 2.3 million inhabitants), which might contribute to the relatively high presence of IV drug abuse among endocarditis patients at KUH. Studies of patients with IE in the USA in 2012-2013 showed a lower incidence of IV drug abuse among IE patients (6.5-7.8% of the IE patients had IV drug abuse) than in our results (32% of the patients had a history of IV drug abuse), although recent US and European studies have noted that the presence of IV drug abuse is generally increasing among patients with IE[23,24]. The high prevalence of IV drug abusers among the IE-patients have affected the association between S. aureus and tricuspid valve vegetation found in this study.…”
contrasting
confidence: 86%
“…Чаще всего при ИЭ правых отделов сердца поражается трикуспидальный клапан -до 100 % при ИЭ наркоманов [4,9,10] и у 56,4-82 % больных, не применявших наркотики [5,11]. Другие возможные локализации ИЭ в правых отделах: электроды ЭКС, клапан легочной артерии (ЛА), Евстахиев клапан, Тебезиев клапан, другие малые врожденные аномалии правого предсердия и пристеночное расположение [3,12].…”
unclassified
“…Другие возможные локализации ИЭ в правых отделах: электроды ЭКС, клапан легочной артерии (ЛА), Евстахиев клапан, Тебезиев клапан, другие малые врожденные аномалии правого предсердия и пристеночное расположение [3,12]. Вовлечение клапана ЛА наблюдается в 0,5-2,9 % всех случаев ИЭ у взрослых [2,3,9] и в 3-20,5 % случаев ИЭ правых отделов сердца, обычно в комбинации с поражением трикуспидального клапана [3,5,9,13].…”
unclassified